+0  
 
0
12
3
avatar+39 

how do i figure this out?? ax^2+bx+c

 Feb 15, 2024
 #1
avatar+1622 
+1

ax^2 + bx + c = 0

Use the quadratic formula, \(x = {-b \pm \sqrt{b^2-4ac} \over 2a}\)

 Feb 15, 2024
 #2
avatar+39 
0

thank you, but is there a way of solving it without using the quadratic formula?

 Feb 15, 2024
 #3
avatar+128732 
+2

sqrt ( 2085136k^4)  = 1444k^2

 

sqrt ( 4100625)   = 2025

 

Note that  2 (1444k^2) (2025)   = 5848200k^2

 

So

 

(1444k^2 - 2025)^2   = 0

 

Take  the sqrt

 

1444k^2  -  2025   = 0

 

1444k^2   = 2025           take  both sqrts 

 

38k  = 45                    38k   = -45

 

k = 45 / 38                  k = -45/38

 

 

cool cool cool

 Feb 16, 2024

0 Online Users